Alcohol Intake and Risk of Injury - Cremonte, Mariana (2014)
Injuries constitute a leading cause of morbidity and mortality in the world, with intentional injuries and those related to traffic most important, due to their social impact and high prevalence. Although alcohol consumption has been identified as a risk factor for injuries, few studies have assessed risk separately for intentional injuries and unintentional injuries caused by traffic, and by other causes. The objective of this pa- per was to estimate the risk of injuries after acute alcohol consumption for intentional injuries and unintentional traffic and non-traffic injuries, using, alternatively, two exposure measures: self-reported drinking prior to the event and blood alcohol concentration. A probability sample was collected of 540 patients from the emergency department of a hospital in Argentina. Logistic regressions were performed, with and without adjusting for gender, age and drinking pattern. Higher risks were found when blood alcohol concentration was used as a measure of consumption, compared to self-report. The highest risk estimates were obtained for intentional injuries, followed by unintentional traffic and, lastly, by unintentional non-traffic injuries. After controlling for confounders, risks for intentional and unintentional traffic injuries appeared similar for those above and below the legal limit. Results point to a significant involvement of alcohol in the regional context. Resumen: Ingesta de alcohol y riesgo de lesiones. Las lesiones constituyen una de las causas principales de morbi-mortalidad. La ingesta aguda de alcohol ha sido identificada como un factor de riesgo importante. Sin embargo, muy pocos estudios han explorado el nivel de riesgo de forma separada para lesiones intencionales y no intencionales causadas por siniestros de tráfico y por otras causas, lo que constituye el principal objetivo de este artículo. Se recolectaron datos de una muestra probabilística (n = 540) de pacientes ingresantes al servicio de emergencia de un hospital interzonal, en Mar del Plata, Argentina. Se efectuaron regresiones logísticas utilizando pacientes no lesionados como grupo control. Cuando el riesgo se evaluó usando nivel de alcohol en sangre como medida de consumo agudo en lugar de autoinforme, los riesgos hallados fueron más elevados. En cuanto a los grupos de causas, la magnitud de riesgo fue mayor para las lesiones intencionales, en segundo lugar para las no intencionales por tránsito y en tercero para las no intencionales por otras causas. Luego de ajustar posibles factores de confusión (edad, género y patrones de consumo habitual de alcohol) las estimaciones de riesgo para lesiones intencionales y no intencionales por tránsito fueron similares entre aquellos con niveles de alcohol en sangre por debajo y por encima del límite legal. Los resultados presentados indican que, en la región, la ingesta de alcohol es un factor de riesgo importante de lesiones.